2009
DOI: 10.1001/archoto.2009.117
|View full text |Cite
|
Sign up to set email alerts
|

First-Choice Treatment in Mild to Moderate Obstructive Sleep Apnea

Abstract: Similar comparison results with nasal CPAP in objective and subjective variables make single-stage, multilevel TCRFTVR a good alternative in primary treatment of mild to moderate obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Two trials, one RCT by Woodson et al. and another non‐RCT by Ceylan et al., compared temperature‐controlled radiofrequency tissue ablation (TCRFTA) of the tongue and palate to CPAP, both finding minimal differences between the two on objective PSG parameters and subjective parameters such as the ESS 1495–1497 . Another study by Weaver et al.…”
Section: Surgical Treatment For Osamentioning
confidence: 99%
See 1 more Smart Citation
“…Two trials, one RCT by Woodson et al. and another non‐RCT by Ceylan et al., compared temperature‐controlled radiofrequency tissue ablation (TCRFTA) of the tongue and palate to CPAP, both finding minimal differences between the two on objective PSG parameters and subjective parameters such as the ESS 1495–1497 . Another study by Weaver et al.…”
Section: Surgical Treatment For Osamentioning
confidence: 99%
“…Two trials, one RCT by Woodson et al and another non-RCT by Ceylan et al, compared temperature-controlled radiofrequency tissue ablation (TCRFTA) of the tongue and palate to CPAP, both finding minimal differences between the two on objective PSG parameters and subjective parameters such as the ESS. [1495][1496][1497] Another study by Weaver et al compared a cohort of patients who had undergone UPPP versus prescribed CPAP treatment and found that the CPAP patients had a 31% higher mortality. 1498 Despite limitations, these data suggest that there may be a phenotype of patient who may benefit from interventions other than CPAP as the first line.…”
Section: Ixa3 Surgery As Primary Treatment For Osamentioning
confidence: 99%
“…After excluding duplicates, the title and abstract of 68 articles were examined, and 39 full‐text articles were assessed for eligibility. Eventually, six studies, including five cohort studies and one non‐randomised clinical trial study, completely met the inclusion criteria and were further enrolled for analysis 17–22 . Figure 1 shows the flowchart of the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Most OSA patients have multilevel disease; hence, nasal, oropharyngeal and palatal, and hypopharyngeal treatment measures are required to improve the airway [ 7 ]. Waite et al first presented a multilevel procedure in 1989 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%